Pemahaman Pendidik PAUD Terkait Kompetensi Pedagogik Menurut Konsep Ki Hadjar Dewantara - Fikriyah Nurul Mufidah; Kuswanto Kuswanto (Universitas Muhammadiyah Surabaya, 2020)
Abstract: The educator is a very important person in the world of education where the learning process with students will determine the future they will live. Especially PAUD educators who will instill various aspects of the foundation in learning to their students. Therefore, the understanding of educators related to one of the competencies that must be possessed, namely pedagogical competence is needed to support good education as professional educators. The pedagogical competence itself is inseparable from an important figure in education, namely Ki Hajar Dewantara who is a well-known figure in the world of education who came to be known as the Father of Indonesian Education who gave birth to a concept of momong, among, and ngemong who until now had an influence in the world. education in Indonesia. The purpose of this study was to find out about educators' understanding of pedagogical competencies according to the Ki Hajar Dewantara concept. By using descriptive analytical qualitative methods by taking various journals and books as a reference. The results obtained are still very lack of understanding of early childhood educators related to pedagogical competence. Which is caused by the lack of PAUD educator insight on teacher competency standards, as well as the lack of implementation of the training or training that he has participated in. Therefore, it is very important for PAUD educators to be able to understand pedagogical competency standards to be able to become professional educators who can educate a qualified generation according to the Ki Hajar Dewantara concept.